2016
DOI: 10.1095/biolreprod.115.134692
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of d-Aspartate on Spermatogenesis in Mouse Testis1

Abstract: Spermatogenesis is controlled by hormonal secretions from the hypothalamus and pituitary gland, by factors produced locally in the testis, and by direct interaction between germ cells and Sertoli cells in seminiferous tubules. Although the mammalian testis contains high levels of D-aspartate (D-Asp), and D-Asp is known to stimulate the secretion of testosterone in cultured Leydig cells, its role in testis is unclear. We describe here biochemical, immunohistochemical, and flow cytometric studies designed to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Although all DA treatments resulted in significant improvement in fertility, motility and plasma membrane integrity compared with control, the moderate level of treatment (DA200) was significantly better when compared with the other DA treatments. The diminished return from increasing the dose of DA can be explained by the fact that the DA concentration is controlled by DA oxidase in Sertoli cells, which catalyses DA degradation to oxaloacetate, ammonium and hydrogen peroxide (Tomita et al 2016). The resulting increase in hydrogen peroxide production in the group treated with the higher dose (300 mg kg À1 day À1 ) in the present study may have attenuated some of the positive effects of DA on the investigated traits.…”
Section: Discussionmentioning
confidence: 56%
“…Although all DA treatments resulted in significant improvement in fertility, motility and plasma membrane integrity compared with control, the moderate level of treatment (DA200) was significantly better when compared with the other DA treatments. The diminished return from increasing the dose of DA can be explained by the fact that the DA concentration is controlled by DA oxidase in Sertoli cells, which catalyses DA degradation to oxaloacetate, ammonium and hydrogen peroxide (Tomita et al 2016). The resulting increase in hydrogen peroxide production in the group treated with the higher dose (300 mg kg À1 day À1 ) in the present study may have attenuated some of the positive effects of DA on the investigated traits.…”
Section: Discussionmentioning
confidence: 56%
“…It is well known that stem cell factor/Kitlg (more commonly known as c-kit) signal induces spermatogonial proliferation. In contrast, Tomita and co-workers [ 54 ] found a negative effect of d -Asp on the differentiation of premeiotic germ cells.…”
Section: D -Asp and Spermatogonial Proliferatiomentioning
confidence: 88%
“…Recently, Tomita and coworkers [ 54 ] have demonstrated that in mouse endogenous d -Asp preferentially accumulates in differentiated spermatids, indicating either transport of d -Asp from other cell type(s) or de novo synthesis in these cells.…”
Section: D -Asp and Spermatozoa Maturationmentioning
confidence: 99%
“…The increase of L-Asp could be explained by the increase in oxaloacetate level which, via glutammic-oxaloacetic transaminase [ 35 ], can be converted into L-Asp in an almost equilibrium reaction. On the other hand, D-Asp levels were shown to increase in mice testis during development [ 36 ].…”
Section: Discussionmentioning
confidence: 99%